Pengaruh Inflasi, Bi-7 Day (Reverse) Repo Rate, dan Nilai Tukar Rupiah (IDR/USD) Terhadap Indeks Harga Saham di Jakarta Islamic Index (JII) Periode Juli 2018 – Juni 2023 - Lia Nirawati; Dwiana, Ninda Amaliatus (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to observe the effect of Inflation, BI-7 Day (Reverse) Repo Rate, and Rupiah Exchange Rate (IDR/USD) on the Jakarta Islamic Index (JII) Stock Price Index simultaneously and partially. This type of research is associative research with a quantitative approach. The data used in this study are secondary in nature obtained from official sources online in the form of monthly summary reports. The research population consists of monthly time series data totaling 60 samples from the period July 2018 to June 2023. The analysis was carried out using multiple linear regression and hypothesis testing with the F test and t test. The research findings show that simultaneously, the three variables have a significant impact on the Share Price Index in the Jakarta Islamic Index (JII) with the F test value revealing findings that exceed the critical value of Ftabel by 30.860 ≥ 2.77. Partially, the Inflation variable (X1) has a positive and significant impact with a t-test value that exceeds the critical value of t table of 3.021 ≥ 2.003, the BI-7 Day (Reverse) Repo Rate variable (X2) also shows a positive and significant impact with a t-test value that exceeds the critical value of t table of 4, 791 ≥ 2.003, while the Rupiah Exchange Rate (IDR/USD) (X3) variable has a negative and significant impact on the Jakarta Islamic Index (JII) Stock Price Index (Y) with a t-test value that exceeds the critical value of the t table of -6.760 ≤ -2.003.